Coordination contracts and numerical analysis of low-carbon competitive supply chains under the influence of low-carbon goodwill - Xie, De-ru; Qin, Qin; Xie, Jian-min; He, Xin-jing; Jiang, Mao-ting (Frontiers in Environmental Science, 2023)
The low-carbon advertising invasion of vendors is a chance for decarbonization and market position enhancement, as well as an opportunity to further investigate the value of low-carbon advertising, under the twin opportunities of low-carbon consumption preference and online consumption platforms. The purpose of this research is to investigate the contractual options of green vendors' online channels engaging in low-carbon advertising competitions under the effect of low-carbon goodwill, as well as to simulate and evaluate the contractual choices of supply chain members.uni-directional and bi-directional cost-sharing covenants under low-carbon competition are designed to coordinate the vicious competition in the supply chain and to give supply chain participants the right of contractual choice through the innovative application of the traditional low-carbon goodwill model and the introduction of the low-carbon advertising competition intensity coefficient.The results show that, under the low-carbon advertising competition decision, the manufacturer has an absolute low-carbon market advantage, but the benefits of all supply chain members are diminished, and, interestingly, the manufacturer who dominates the market is the contract agreement's facilitator.Second, well-designed pacts may give producers and merchants with greater low-carbon strategic alternatives. Although both uni-directional and bi-directional cost-sharing pacts can yield Pareto gains in advertising competition for the supply chain and its members, bi-directional cost-sharing pacts outperform uni-directional pacts in terms of coordination advantages. Furthermore, the important discovery is that bigger profit increases may be attained by contractual collaboration in low-intensity advertising competition. As a result, moderate rivalry is desirable, whereas excessive competitiveness would harm the supply chain system. Manufacturers should aggressively urge retailers to collaborate in order to optimize profit and establish long-term and stable cooperative ties between upstream and downstream firms in the green supply chain.